The role of retrotransposons in gene family expansions: insights from the mouse Abp gene family - Janoušek, Václav; Karn, Robert C; Laukaitis, Christina M (BMC evolutionary biology, 2013)
BACKGROUND: Retrotransposons have been suggested to provide a substrate for non-allelic homologous recombination (NAHR) and thereby promote gene family expansion. Their precise role, however, is controversial. Here we ask whether retrotransposons contributed to the recent expansions of the Androgen-binding protein (Abp) gene families that occurred independently in the mouse and rat genomes. RESULTS: Using dot plot analysis, we found that the most recent duplication in the Abp region of the mouse genome is flanked by L1Md_T elements. Analysis of the sequence of these elements revealed breakpoints that are the relicts of the recombination that caused the duplication, confirming that the duplication arose as a result of NAHR using L1 elements as substrates. L1 and ERVII retrotransposons are considerably denser in the Abp regions than in one Mb flanking regions, while other repeat types are depleted in the Abp regions compared to flanking regions. L1 retrotransposons preferentially accumulated in the Abp gene regions after lineage separation and roughly followed the pattern of Abp gene expansion. By contrast, the proportion of shared vs. lineage-specific ERVII repeats in the Abp region resembles the rest of the genome. CONCLUSIONS: We confirmed the role of L1 repeats in Abp gene duplication with the identification of recombinant L1Md_T elements at the edges of the most recent mouse Abp gene duplication. High densities of L1 and ERVII repeats were found in the Abp gene region with abrupt transitions at the region boundaries, suggesting that their higher densities are tightly associated with Abp gene duplication. We observed that the major accumulation of L1 elements occurred after the split of the mouse and rat lineages and that there is a striking overlap between the timing of L1 accumulation and expansion of the Abp gene family in the mouse genome. Establishing a link between the accumulation of L1 elements and the expansion of the Abp gene family and identification of an NAHR-related breakpoint in the most recent duplication are the main contributions of our study.
Keywords: protein vázající androgen; Multigene Family; myši; multigenová rodina; Rats; Sequence Alignment; Mice; duplikace genu; Amino Acid Sequence; Animals; retroelementy; fylogeneze; Rodentia; Gene Duplication; molekulární sekvence - údaje; zvířata; sekvenční seřazení; hlodavci; Retroelements; Molecular Sequence Data; krysa rodu Rattus; sekvence aminokyselin; Androgen-Binding Protein; Phylogeny